Soluble RANKL expression in Lactococcus lactis and investigation of its potential as an oral vaccine adjuvant. (December 2015) - Kim, Jeong-In; Park, Tae-Eun; Maharjan, Sushila; Li, Hui-Shan; Lee, Ho-Bin; Kim, In-Seon; Piao, Dachuan; Lee, Jun-Yeong; Cho, Chong-Su; Bok, Jin-Duck; Hong, Zhong-Shan; Kang, Sang-Kee; et al.
Abstract Background To initiate mucosal immune responses, antigens in the intestinal lumen must be transported into gut-associated lymphoid tissue through M cells. Recently, it has been increasingly recognized that receptor activator of NF-kB ligand (RANKL) controls M cell differentiation by interacting with RANK expressed on the sub-epithelium of Peyer's patches. In this study, we increased the number of M cells using soluble RANKL (sRANKL) as a potent mucosal adjuvant. Results For efficient oral delivery of sRANKL, we constructed recombinantLactococcus lactis (L. lactis ) IL1403 secreting sRANKL (sRANKL-LAB). The biological activity of recombinant sRANKL was confirmed by observing RANK-RANKL signaling in vitro. M cell development in response to oral administration of recombinantL. lactis was determined by 1.51-fold higher immunohistochemical expression of M cell marker GP-2, compared to that of non-treatment group. In addition, an adjuvant effect of sRANKL was examined by immunization of mice with M-BmpB as a model antigen after treatment with sRANKL-LAB. Compared with the wild-typeL. lactis group, the sRANKL-LAB group showed significantly increased systemic and mucosal immune responses specific to M-BmpB. Conclusions Our results show that the M cell development by sRANKL-LAB can increase the antigen transcytotic capability of follicle-associated epithelium, and thereby enhance the mucosal immune response, which implies that oral administration of sRANKL is a promising adjuvant strategy for efficient oral vaccination.